CordelSextilha.BR: A Benchmark for Poetic Form in Brazilian Cordel Verse Generation - Barbosa, Bryan K. S.; Barbosa, Marcela Y. A. (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2025)
We introduce CordelSextilha.BR, the first benchmark for automatic generation of Brazilian cordel sextilhas. We compile 1,519 public-domain stanzas, remove the final line, and gather expert ratings for rhyme, meter, coherence, and “cordelisticity”. Rule-based metrics (RhythmAcc, RhymeAcc) align with human judgements; GPT-4o and LLaMA-3.2 (8B) reach about 80% rhyme and about 75% rhythm accuracy. The corpus, metrics and baselines enable RLHF research in low-resource poetry.